Prediction of the critical gas flow rate for avoiding liquid accumulation in natural gas pipelines. (September 2020) - Bissor, E. Hamami; Yurishchev, A.; Ullmann, A.; Brauner, N.
Abstract: Natural gas pipelines that connect subsea fields to shore terminals are composed of horizontal and inclined sections. The smooth transportation of the gas is challenged by the transient flow phenomena associated with the liquid accumulation problem and its displacement along such pipelines. The current study is focused on the estimation of the critical gas flow rate required for avoiding liquid accumulation in the low sections of high-pressure, large-diameter gas pipelines. Results obtained from transient numerical simulations, which were substantiated by air-liquid experiments, were used to establish new mechanistic models. The models enable predicting the effect of the system parameters on the critical gas flow rate required for purging-out the liquid from the pipeline system. Effects of gas pressure, pipe diameter and inclination, surface wetting, and liquid viscosity were considered. The prediction of the liquid propagation velocity in upward inclined pipe sections at supercritical flow rates was also addressed. The predictions obtained by the new mechanistic models were found to be consistent with the experimental and simulation results and showed a similar dependence on the various system parameters and operational conditions. The obtained values for the critical gas velocities are much lower than those predicted by models suggested in the literature for the stabilization of upward gas-liquid flow. The model can provide a useful tool for flow assurance in natural gas transportation pipelines.